The Research on the Ethical Motivation and Teaching Ability Using Jigsaw II Cooperative Learning Technique of Teachers in Rural Inclusive Kindergartens in Guangxi - Jingling , Zhang; Bhothisarn, Phitorn (วารสารวิทยาลัยนครราชสีมา สาขามนุษยศาสตร์และสังคมศาสตร์, 2026)
This study aimed to achieve the following objectives: (1) To compare changes in ethical motivation test scores among teachers at a rural inclusive kindergarten in Guangxi before and after ethical training; (2) To conduct comparative analysis between teachers 'teaching ability test results and the standard threshold of 80% full score; and 3) To evaluate teachers' satisfaction with the correlation between their ethical motivation and teaching ability. The study adopted a single-group pretest posttest design, with samples selected from 25 in-service teachers at a rural inclusive kindergarten in Guangxi through comprehensive sampling.The research tools included: 1) An ethical motivation training program based on teacher ethical norms; 2) A 40-item multiple-choice ethical motivation assessment and a 35-item multiple-choice teaching ability assessment; 3) A teacher satisfaction questionnaire comprising 18 items and 5 rating levels. The data analysis employed statistical methods that was mean, percentage, standard deviation, and t-test. The results were as follows: (1) The scores of teachers' ethical motivation test were significantly higher than those before the training (X=68.52, S.D.=7.31; X=82.15, S. D.=5.48, t=8.92, p<0.01). (2) At the 0.01 significance level, the test scores of teachers' teaching ability was significantly higher than the 80% full-score threshold (test score X=83.67, S.D.=4.93, t=4.15, p<0.01). and (3) The highest satisfaction was for the correlation between ethical motivation and teaching ability, and the second was for the synchronicity of ethical training and teaching ability.